DIMENSI SPIRITUAL KEBUDAYAAN: Di Tengah Relasi yang Timpang Antara Utara dan Selatan - Tasrif, Muhammad (El-HARAKAH (TERAKREDITASI), 2010)
Moslem society as a part of the population of the south world, culturally is in the influence of the hegemony of non-Moslem culture. Mainly, European, American, and Australian as parts of the north world population. Until the mid twentieth century, the hegemony existed in the form of military imperialism. Meanwhile, in post-mid twentieth century, the hegemony changed into cultural imperialism in many areas, such as, social, economic, and art. The countries of the south world have really done some efforts to face the neo-imperialism, but have not succeeded well. Therefore, more serious efforts should be done to face the neo-imperialism, that is, the creativity to make the European and American cultural products as materials that can be creatively rearranged and matched with the local culture. In the creative process, the spiritual dimension of culture should become the basis of cultural production process at present and in the future to create a fair relation. The use of spiritual dimension of culture can create new cultural products. In turn, the cultural products of the south world will exist, and finally they can be exchanged with the products of the north world. This is what China is doing with its developing economic power to balance out the domination of Europe and America. The same hopefully appears from the Islam world although it needs more serious cultural works. According to Faisal Ismail, the awakening of Islam and its culture depends on the Moslems themselves, depends on their cultural works they do.